Percutaneous Transcatheter Closure of Ruptured Sinus of Valsalva Aneurysm: Immediate Result and Long-Term Follow-Up - Sinha, Sudhir Chandra; Sujatha, Vipperla; Mahapatro, Anil Kumar (International Journal of Angiology, 2015)
There is scarcity of data on closure and long-term follow-up of percutaneous treatment of ruptured sinus of Valsalva aneurysm (RSOVA). In this article, we present our experience in percutaneous closure of this defect. Between December 2009 and July 2014, 11 cases of RSOVA were referred to our hospital. Eight of the 11 cases (72.7%) were considered for percutaneous closure. Seven of the eight (87.5%) patients underwent successful percutaneous closure. There were four females and three males in the age group of 16 to 48 years (mean 24.7 ± 6.1 years). Associated defects were bicuspid aortic valve in one patient, mild preexisting aortic regurgitation in two patients, and healed infective endocarditis in one patient. Echocardiography revealed RSOVA from right coronary sinus (RCS) to right atrium (RA) in one patient (14.3%), RCS to right ventricular outflow in three patients (42.8%), and noncoronary sinus ruptured into RA in three patients (42.8%). All patients were symptomatic in New York Heart Association (NYHA) class II to IV. The defect size ranged from 7 to 10 mm (mean 8.4 ± 1.3 mm). The defects were closed from the venous side with device selection 2 to 4 mm higher than the defect size under fluoroscopy and transesophageal echocardiography guidance. Technical success was 87.5%. The mean device size was 12.0 ± 1.6 mm/10.0 ± 1.6 mm. Six out of seven patients (85.7%) had complete disappearance of shunt before discharge. During 1 to 55 months follow-up, all patients were in NYHA class I. There was no residual shunt, progression of AR or new AR, infective endocarditis or device embolization. Percutaneous closure of RSOVA appears to be a safe alternative to surgical therapy, with high technical success and excellent long-term outcome.
Keywords: aneurysm; cardiac catheterization; cardiac device; endocarditis; endovascular procedure; percutaneous; cardiac surgery